Sustainable Financial Strategies in the Management of BUMDes Ponggok Ecotourism (Case Study of the Village with the Highest Income in Klaten) - Rasmawati A.R.; Siti Mulasih; Fitry Nur Hidayanti; Mukhlis Aldi Dermawan; Muhammad Nurdin (Goodwood Publishing, 2026)
Purpose: This study aims to analyze the sustainable financial strategies of BUMDes Ponggok, reveal the factors supporting its success, and formulate a financial model that can be replicated by other BUMDes. Research Methodology: This study uses a qualitative method supported by quantitative data and an exploratory case study approach. The main stages of the research are as follows: (1) identification and collection of data through in-depth interviews with BUMDes managers, village officials, and local communities; (2) data processing and analysis through interview transcription, data coding, and thematic analysis; (3) data validation through data triangulation techniques from various sources; and (4) presentation and drawing of conclusions to answer the research questions. Results: The analysis shows that BUMDes Ponggok’s sustainable financial strategy is formed from a combination of sound financial planning, operational efficiency, transparency in reporting, utilization of digital technology, and risk management. This approach is in line with the principles of sustainable finance, which emphasize a balance between economic profit, environmental sustainability, and community welfare. Conclusions: This study is limited to the case of BUMDes Ponggok; therefore, the results are contextual. However, the resulting sustainable financial strategy model can still be used as a starting point for other BUMDes with adjustments based on local conditions. Limitations: This study focuses only on BUMDes Ponggok; therefore, the findings are contextual, although the model is adaptable to other settings. Contributions: This study enriches the financial and ecotourism management literature and offers a practical reference for village enterprises in developing businesses based on local potential.